2018
DOI: 10.2196/jmir.8550
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Electronic Cigarette Brands From 2013-2014 to 2016-2017: Analysis of Brand Websites

Abstract: BackgroundThe electronic cigarette (e-cigarette) industry has grown in size and organizational complexity in recent years, most notably with the entry of major tobacco companies in 2012 and the proliferation of vape shops. Many brands maintain retail websites that present e-cigarette marketing claims and sell directly to consumers. Understanding of the evolving composition of different types of e-cigarette brand websites is currently underdeveloped.ObjectiveThis paper presents how e-cigarette brand websites su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
76
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(81 citation statements)
references
References 35 publications
2
76
0
3
Order By: Relevance
“…This is in line with another study that looked at JUUL flavor usage in middle-schoolers and high-schoolers, which showed that fruit-flavored pods like mango and fruit were preferred by this young cohort [23]. Despite the fact that e-cigarettes were first introduced to the market in 2007, there has been a rapid market expansion with the amount of unique flavors more than doubling from 2013-2014 to 2016-2017, with 15,568 distinct flavors being sold [24]. With this continuously changing product, future studies should be conducted in a longitudinal model with a larger cohort, looking at immunoglobulin, pro-inflammatory, and oxidative stress biomarkers in e-cigarette users and non-users, with a specific interest in the flavoring effects on these biomarkers.…”
Section: Discussionsupporting
confidence: 81%
“…This is in line with another study that looked at JUUL flavor usage in middle-schoolers and high-schoolers, which showed that fruit-flavored pods like mango and fruit were preferred by this young cohort [23]. Despite the fact that e-cigarettes were first introduced to the market in 2007, there has been a rapid market expansion with the amount of unique flavors more than doubling from 2013-2014 to 2016-2017, with 15,568 distinct flavors being sold [24]. With this continuously changing product, future studies should be conducted in a longitudinal model with a larger cohort, looking at immunoglobulin, pro-inflammatory, and oxidative stress biomarkers in e-cigarette users and non-users, with a specific interest in the flavoring effects on these biomarkers.…”
Section: Discussionsupporting
confidence: 81%
“…The NAS considered toxicity of flavorings, with little attention to attraction among youth despite the US Surgeon General concluding that many ENDS flavors are marketed to youth [4]; flavor varieties now exceed 15 500 [9], including 'Hello Kitty' and cotton candy. For example, the European Union (EU) and Canada restrict ENDS advertising to youth; the EU requires graphic health warnings and limits the nicotine strength of e-liquid to ≤ 20 mg/ml, and Canada bans confectionary ENDS flavors.…”
mentioning
confidence: 99%
“…This occurs primarily through masking the initial harshness of nicotine/tobacco that is aversive to new and beginning smokers and therefore increases smoking initiation [ 12 , 13 ]. Although non-menthol flavors are banned in combustible cigarettes, >15,000 flavor options are available for ENDS products with a 67% increase in flavor production from 2013 to 2014 [ 14 , 15 ]. In 2019, more than 50% and 60% of high school users used menthol and fruit flavored ENDS, respectively, and more than half of ENDS users prefer flavored products [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%